2018
DOI: 10.3389/fped.2018.00149
|View full text |Cite
|
Sign up to set email alerts
|

Is Decellularized Porcine Small Intestine Sub-mucosa Patch Suitable for Aortic Arch Repair?

Abstract: Introduction: We reviewed our experience with decellularized porcine small intestine sub-mucosa (DPSIS) patch, recently introduced for congenital heart defects.Materials and Methods: Between 10/2011 and 04/2016 a DPSIS patch was used in 51 patients, median age 1.1 months (5 days to 14.5 years), for aortic arch reconstruction (45/51 = 88.2%) or aortic coarctation repair (6/51 = 11.8%). All medical records were retrospectively reviewed, with primary endpoints interventional procedure (balloon dilatation) or surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Multiple investigators have reported failures with SIS over the past 10 years, both in preclinical and clinical scenarios. 25 , 26 , 36 , 37 , 38 , 39 , 40 However, several papers have focused on this biomaterial used as a valve leaflet patch and/or in high pressure districts 37 , 40 ; moreover, histologic changes in preclinical studies were mostly assessed on nonseeded grafts. 23 , 24 , 25 , 27 It could be argued that seeded porcine SIS might not exhibit the same behavior observed in this work when implanted in humans as a result of cross-species immune reaction to the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigators have reported failures with SIS over the past 10 years, both in preclinical and clinical scenarios. 25 , 26 , 36 , 37 , 38 , 39 , 40 However, several papers have focused on this biomaterial used as a valve leaflet patch and/or in high pressure districts 37 , 40 ; moreover, histologic changes in preclinical studies were mostly assessed on nonseeded grafts. 23 , 24 , 25 , 27 It could be argued that seeded porcine SIS might not exhibit the same behavior observed in this work when implanted in humans as a result of cross-species immune reaction to the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Важливим фактором, що впливає на віддалені результати є кальцифікація з часом будь-яких біологічних матеріалів, які використовують для пластики дуги аорти, в тому числі й аутоперикарда. Проте дослідження показують нижчу здатність аутоперикарда до кальцифікації, ніж в інших біоматеріалів [6]. Ще одним важливим питанням є аневризмоутворення у віддаленому періоді після використання як біологічних, так і синтетичних матеріалів для пластики аорти.…”
Section: таблиця 1 перелік супутніх ввс поєднаних з гіпоплазією дугиunclassified
“…Dobrilovic and colleagues [4] reported early catastrophic patch disruption in 2 patients and pseudoaneurysm in 1 patient who had undergone femoral artery endarterectomy and patchplasty with ECM because of peripheral artery disease. Corno and coworkers [5] reported a 25.5% rate of reintervention in 51 patiens who had undergone aortic arch reconstruction or aortic coarctation repair, and the reason for the reintervention was the obstruction in the ECM patch used to enlarge the aortic arch/isthmus.…”
Section: Aneurysmal Degeneration Of Extracellular Matrix In Arterial Reconstructionmentioning
confidence: 99%